A Luta Continua1: Next Steps for Racism Research Among Black American Youth. (20th October 2020) - Seaton, Eleanor K.
Abstract: Research examining the impact of racism among Black American children and adolescents has exploded in recent years. Given what we have learned about racism among Black American youth, in this article, I provide recommendations for developmental scientists. First, we need to examine other types of racism‐related stressors, namely internalized racism, vicarious racism, environmental racism, Internet assessments of racism, and racial macro stressors. A recent racial macro stressor that should be studied is Covid‐19, which has had devastating effects on the Black American community. Second, we need to examine middle childhood and adolescence as early periods of accelerated aging due to experiencing racism early in life. Adolescence may be a sensitive period given research illustrating that experiences of racial discrimination in adolescence affect adult health. Measurement is critical because these recommendations cannot be realized without developing new measures and incorporating diverse methods.